2009
DOI: 10.1089/cbr.2009.0629
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitor, Valproic Acid, Induces p53-Dependent Radiosensitization of Colon Cancer Cells

Abstract: Agents that inhibit histone deacetylases (HDAC inhibitors) have been shown to enhance radiation response. The aim of this study was to evaluate the effects of low, minimally cytotoxic concentrations of the HDAC inhibitor, valproic acid (VPA), on radiation response of colorectal cancer cells. Cell lines LS174T and an isogenic pair of HCT116, which differed only for the presence of wild-type p53, were exposed to ionizing radiation (IR) alone, VPA alone, or the combination. Clonogenic survival, g-H2AX induction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 42 publications
3
78
0
Order By: Relevance
“…These studies show that VPA in vitro enhances radiosensitivity in malignant glioma (20,22), colorectal carcinoma (21), leukemia (23,24,26,27) and retinoblastoma cells (25). Moreover, a corresponding enhancement of therapeutic efficacy in vivo was also reported when VPA was combined with irradiation (20,21). To our knowledge, there are currently four on-going phase I clinical trials assessing the combination of HDAC inhibitors and radiotherapy: VPA with radiotherapy for pediatric glioma, VPA with radiotherapy for pediatric refractory solid and central nervous system (CNS) tumors, VPA or hydralazine with CRT for cervical cancer, and vorinostat with palliative radiotherapy (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These studies show that VPA in vitro enhances radiosensitivity in malignant glioma (20,22), colorectal carcinoma (21), leukemia (23,24,26,27) and retinoblastoma cells (25). Moreover, a corresponding enhancement of therapeutic efficacy in vivo was also reported when VPA was combined with irradiation (20,21). To our knowledge, there are currently four on-going phase I clinical trials assessing the combination of HDAC inhibitors and radiotherapy: VPA with radiotherapy for pediatric glioma, VPA with radiotherapy for pediatric refractory solid and central nervous system (CNS) tumors, VPA or hydralazine with CRT for cervical cancer, and vorinostat with palliative radiotherapy (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 98%
“…In mammalian cells, DSBs are repaired mostly by either homologous recombination (HR) or non-homologous end-joining (NHEJ). Several HDAC inhibitors including VPA can downregulate DNA repair proteins related to HR (Rad51) (33)(34)(35) and NHEJ (Ku70, Ku86 and DNA-PKcs) (21,(34)(35)(36)(37)(38)(39)(40). Munchi et al (38) noted that sodium butylate suppresses Ku70, Ku86 and DNA-PKcs at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are especially seen when it is used in combination with IIF. The dual combination enhances Bax expression while Bcl-2 expression is markedly reduced [7]. TIMP-1 activity is also enhanced at the same time, while MMP2 activity is considerably reduced.…”
mentioning
confidence: 94%
“…Both transcriptional and nontranscriptional mechanisms of action have been investigated [15]. Pre-clinical studies using cell lines from a variety of gynecologic [16][17][18] and other malignancies [19,20] have demonstrated that natural and synthetic HDAC inhibitors can inhibit tumor cell growth in vitro and in vivo through cell cycle arrest as well as the induction of mitotic defects through histone mediated and histone independent interactions [15]. Investigations utilizing in vitro and in vivo models of ovarian cancer have demonstrated that HDAC inhibition synergizes with conventional chemotherapies to induce potent cytotoxic effects supporting the potential use of this combination in the clinic [18,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%